Effects of Bamboo Shoot Dietary Fiber on Mechanical Properties, Moisture Distribution, and Microstructure of Frozen Dough - Hua Zhang; Yanyan Zhang; Xintian Wang; Qisen Xiang; Yanhong Bai; Suyun Li; Lixin Yang (Journal of Chemistry)
In this paper, the effects of Bamboo shoot dietary fiber (BSDF) on the mechanical properties, moisture distribution, and microstructure of frozen dough were investigated. The state and distribution of water in frozen dough was determined by differential scanning calorimetry (DSC) and low-field nuclear magnetic resonance (LNMR) spectroscopy. The microstructure of frozen dough was studied. The structure of the gluten protein network found in wheat flour dough was studied by scanning electron microscopy (SEM). The result showed that the BSDF could significantly improve the viscoelasticity and extensibility of frozen dough after thawing in a dose-dependent manner. It was significantly improved with the increase in the addition amount of BSDF (P<0.05). DSC analysis showed that the freezable water content and thermal stability of frozen dough were increased after the addition of BSDF. LNMR analysis showed that the appropriate (<0.1%) addition amount of BSDF could significantly (P<0.05) decline the contents of bound water. Meanwhile, the loose bound water and free water were raised significantly (P<0.05) after the addition of BSDF. Moreover, the addition of BSDF induces arrangement of starch granule and gluten network in frozen dough. BSDF can be used as a novel quality improver of frozen dough.